Variability in presentation and management of gastric volvulus: report of 3 cases - Peña-González, Ricardo-Raziel; Huerta-Pérez, Ramón-Guillermo; Hernández, Erick-F.; Higuera-Hidalgo, Francisco; Etchegaray-Dondé , Agustin (International Journal of Research in Medical Sciences, 2023)
Gastric volvulus is a pathology of acute or subacute presentation. Depending on the type, a gastric volvulus can present as an emergency if there is vascular compromise with necrosis and high risk of perforation and its surgical resolution is mandatory. Subacute gastric volvulus does not compromise the organ or organism urgently but is associated with high morbidity and should be resolved when the patient is in optimal conditions to offer definitive treatment. Depending on the torsion axis, it is classified as axial or mesenteroaxial organ, both merit reduction according to their presentation and the clinical context of the patient.